The Role of Civic Education in Shaping Social Awareness of Elementary School Children - Sri Yunita; Lidya Sitompul; Vista Putri; Fatma Amelia Pane; Imelda Sari Daulay (Universitas Muhammadiyah Enrekang, 2023)
This research aims to explore the role of education in forming children's awareness. Becoming civically aware is increasingly important in complex modern societies, where children need to understand their rights, obligations and responsibilities as citizens. This research uses interview methods with teachers and students. The research results show that citizenship education has an important role in forming children's awareness. Through a relevant curriculum and interactive learning approach, children can learn about the values of democracy, pluralism, tolerance and human rights. Citizenship education also helps children understand their role in building a just and sustainable society. Apart from that, this research also identified several challenges faced in implementing citizenship education, such as a lack of resources and training for teachers, as well as differences in political views that exist in society. Therefore, recommendations are given to strengthen the role of citizenship education through the development of a more inclusive curriculum and better training for teachers. Thus, this research confirms that citizenship education has a significant role in forming children's awareness of their rights, obligations and responsibilities as active citizens and participants in the development of society and the country.